The Influence of Game-Based Learning Using Assemblr Edu on Digital Skills and Critical Thinking of Elementary School Students in Mathematics: Toward Quality Education and Digital Literacy - Sri Winarti; Supri Wahyudi Utomo; Marheny Lukitasari (Postgraduate, University of Mataram, 2026)
This research investigates the influence of Game-Based Learning (GBL) using Assemblr Edu on digital skills and critical thinking of fourth-grade students in mathematics. A quasi-experimental design with nonequivalent control groups compared 22 students from SDN Sidorejo 01 and 02, Wungu District, Madiun Regency. The experimental group received mathematics instruction using GBL with Assemblr Edu incorporating Augmented Reality technology, while the control group received conventional methods. Data collection utilized practical tests for digital skills, written tests measuring critical thinking based on Facione's framework (interpretation, analysis, explanation, evaluation, self-regulation, and inference), and observational methods. Purposive sampling ensured equivalent class sizes and comparable academic achievement. Data analysis employed normality testing, homogeneity testing, paired sample t-tests, and independent sample t-tests. Results revealed significant improvements in the experimental group's digital skills (mean increase=7.73, t=8.942, p<0.001) and critical thinking abilities (mean increase=6.37, t=7.865, p<0.001) compared to the control group (mean increases of 2.18 points each). Independent t-test confirmed significant differences between groups (digital skills: t=7.234, p<0.001; critical thinking: t=6.518, p<0.001). The study demonstrates that integrating game-based pedagogical approaches with augmented reality technology effectively enhances 21st-century competencies in elementary mathematics education, particularly in semi-rural contexts.